2009
DOI: 10.1182/blood-2008-06-162248
|View full text |Cite
|
Sign up to set email alerts
|

Runx2 induces acute myeloid leukemia in cooperation with Cbfβ-SMMHC in mice

Abstract: The core-binding factor (CBF) is a master regulator of developmental and differentiation programs, and CBF alterations are frequently associated with acute leukemia. The role of the CBF member RUNX2 in hematopoiesis is poorly understood. Genetic evidence suggests that deregulation of Runx2 may cause myeloid leukemia in mice expressing the fusion oncogene Cbfb-MYH11. In this study, we show that sustained expression of Runx2 modulates Cbf␤-smooth muscle myosin heavy chain (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 58 publications
5
65
0
Order By: Relevance
“…This could indicate a specific role for EVI1 overexpression in the development of leukemia in these cases, especially as some of these probe sets included genes that have previously been reported to have a role in hematopoiesis and/or the development of leukemias, for example PBX1 and RUNX2. 33,34 Moreover, recent analysis of the Pbx1 promoter region in mice revealed that Evi-1 upregulates Pbx1 transcription. 50 This emphasizes that PBX1 is a possible target gene of EVI1 involved in the leukemogenesis of EVI1 þ patients.…”
Section: Discussionmentioning
confidence: 99%
“…This could indicate a specific role for EVI1 overexpression in the development of leukemia in these cases, especially as some of these probe sets included genes that have previously been reported to have a role in hematopoiesis and/or the development of leukemias, for example PBX1 and RUNX2. 33,34 Moreover, recent analysis of the Pbx1 promoter region in mice revealed that Evi-1 upregulates Pbx1 transcription. 50 This emphasizes that PBX1 is a possible target gene of EVI1 involved in the leukemogenesis of EVI1 þ patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, we focused on BCL11A and TRIM24, both of which have been reported to promote p53 degradation either directly or indirectly (23)(24)(25)(26). Moreover, we Since it has been shown that RUNX family members have redundant functions (9,29,30), we sought to examine the expression levels of the other RUNX family members, RUNX2 and RUNX3, in RUNX1-knockdown AML cells. Under our tetracycline-inducible shRNA expression system, the expression levels of RUNX1 started to decline at 24 hours after doxycycline treatment, when the expression levels of RUNX2 and RUNX3 were unchanged.…”
Section: Runx1 Depletion-mediated Antileukemic Effect Requires Functimentioning
confidence: 99%
“…Below, we focus on Runx1 as the main regulator of hematopoiesis, but also Runx2 and Runx3 express transcripts from 2 promoters to generate alternative isoforms. 94,[111][112][113] Alternative promotor usage contributes to regulatory complexity, with the production of Runx1 transcripts that differ in their 59 and 39 UTRs, their coding sequence, and the time required for their transcription (Figure 3). 46,81,106,114 Differences in the identity and length of the UTRs have been linked to differences in RNA stability and translation efficiency.…”
Section: Structure Of Mammalian Runx Genes and Alternatively Spliced mentioning
confidence: 99%
“…Although Runx2 expression is high in the HSPC compartment of mouse BM, 94 there is no data thus far demonstrating a role for Runx2 in fetal or adult BM HSCs.…”
mentioning
confidence: 99%